Effect of deficit irrigation on the accumulation of antioxidant compounds in tomato plants - Méndez-Vázquez, José Refugio; Benavides-Mendoza, Adalberto; Juárez-Maldonado, Antonio; Cabrera-De la Fuente, Marcelino; Robledo-Olivo, Armando; González-Morales, Susana (Ecosistemas y Recursos Agropecuarios, 2021)
Efficient use of water in agriculture is the key to mitigating scarcity of water resources. Deficit irrigation (DI) is a strategy used that reduces the water supply without affecting the production and quality of the harvest. The objective of this work was to evaluate the effect on antioxidantmetabolism in the flowering and production stage of tomato plants under two levels of DI (50 and 75%) based on evapotranspiration by the gravimetric method during the cultivation cycle. The results showed an increase in the antioxidant activity and ascorbate peroxidase activity in flowering in the treatments with DI, while in production the treatments with DI decreased the total proteins and the antioxidant activity. Tomato plants under DI modified antioxidant metabolism to mitigate oxidative damage due to water deficit.